2013
DOI: 10.1177/0892705712470265
|View full text |Cite
|
Sign up to set email alerts
|

Property enhancement of epoxy resin using a combination of amine-terminated butadiene–acrylonitrile copolymer and nanoclay

Abstract: The present work investigates the effect of organomodified nanoclay (ZW1) and butadiene-acrylonitrile copolymer terminated with amine group (ATBN copolymer) on the properties of epoxy resin (EP). The impact strength (IS) and the critical stress intensity factor (K C ) values of EP containing 1% nanoclay increased approximately by 200% and 75%, respectively, in relation to neat EP. Moreover, hybrid composites containing 1% or 2% nanoclay and ATBN showed improved mechanical properties in relation with unmodified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…It was shown that the addition of 1.5 wt% nanoclay to an epoxy composition modified with 5 wt% ATBN led to synergistic effects on the mechanical behavior [ 101 ]. A similar improvement in the epoxy resin mechanical properties was noted in the case of epoxy resin modified with a combination of ATBN and organomodified nanoclay (Nanobent ZW1) [ 102 ]. Ternary epoxy composites containing 1 wt% or 2 wt% Nanobent and ATBN showed improved mechanical properties in relation to the unmodified EP.…”
Section: Hybrid Epoxy Nanocompositessupporting
confidence: 52%
See 1 more Smart Citation
“…It was shown that the addition of 1.5 wt% nanoclay to an epoxy composition modified with 5 wt% ATBN led to synergistic effects on the mechanical behavior [ 101 ]. A similar improvement in the epoxy resin mechanical properties was noted in the case of epoxy resin modified with a combination of ATBN and organomodified nanoclay (Nanobent ZW1) [ 102 ]. Ternary epoxy composites containing 1 wt% or 2 wt% Nanobent and ATBN showed improved mechanical properties in relation to the unmodified EP.…”
Section: Hybrid Epoxy Nanocompositessupporting
confidence: 52%
“…Similarly to CTBN, liquid butadiene acrylonitrile terminated with amine groups (ATBN) was also used to toughen epoxy nanocomposites [ 101 , 102 , 103 ]. It was shown that the addition of 1.5 wt% nanoclay to an epoxy composition modified with 5 wt% ATBN led to synergistic effects on the mechanical behavior [ 101 ].…”
Section: Hybrid Epoxy Nanocompositesmentioning
confidence: 99%
“…Due to their many superior properties, EPs have a wide range of applications (electronic insulators, coatings, adhesives and aerospace). [2][3][4] They are generally formed as a result of the reaction of two components, Bisphenol (A) and Epichlorhydride (B). Like other thermoset plastics, they go from liquid to solid and reach their final hardness after a period of curing.…”
Section: Introductionmentioning
confidence: 99%